Efeito de auxinas e boro no enraizamento de estacas caulinares de kiwi retiradas em diferentes épocas - Ono, Elizabeth Orika [UNESP]; Rodrigues, Joǎo Domingos [UNESP]; De Pinho, Sheila Zambello [UNESP] (My University, 1998)
This work was carried out to study the effects of some synthetical auxins and boron on the rooting of stem cuttings of kiwi (Actinidia deliciosa Pl. cv. Tomuri). Cuttings of semi-woody stems with two knots and leaves divided in two, with approximately 10 cm of length were utilized. The base of the cuttings received the following treatments: 1) water only; 2) NAA 300 ppm; 3) IBA 300 ppm; 4) NAA 300 ppm + B; 5) IBA 300 ppm + B; 6) NAA 0,5%-talc and 7) IBA 0,5%-talc. After these treatments, the stems were placed in suitable rooting dishes, with pure vermiculite in misty nebulization chamber for 120 days. Evaluations were made based on the following observations: percentage of rooted stem cuttings; reductor sugar and total sugar analyses and tryptophan analyses. The results showed that the autumm season is the best for rooting for kiwi stem cuttings. The exogenous application of 0.5% of IBA talc on the bases of the cuttings showed positive results.

O presente trabalho teve por objetivo verificar os efeitos da época de retirada dos ramos de kiwi (Actidina deliciosa Pl. cv. Tomuri), e da aplicação de auxinas e do boro, sobre o enraizamento de estacas caulinares. Foram utilizadas estacas de ramos semi-lenhosos contendo dois nós e duas folhas cortadas ao meio, com aproximadamente, 10 cm de comprimento. A base das estacas receberam os seguintes tratamentos: 1) água; 2) ANA 300 ppm; 3) AIB 300 ppm; 4) ANA 300 ppm + B; 5) AIB 300 ppm + B; 6) ANA 0,5%-pó e 7) AIB 0,5%-pó. Após o tratamento, estas foram plantadas em bandejas contendo vermiculita pura e colocadas na câmara de nebulização, por 120 dias. Foram realizadas as seguintes avaliações: porcentagem de estacas enraizadas; análise de açúcares redutores e açúcares totais e análise de triptofano. O outono foi a melhor época de coleta dos ramos para produção das estacas caulinares de kiwi, e o processo de enraizamento foi incrementado pela aplicação exógena na base das estacas de AIB, na forma de talco a 0,5%.
Effects of the auxins and boron on the rooting of kiwi stem cuttings collected in the four seasons
Keywords: Actinidia chinensis; Actinidia deliciosa